To speak like an engineer: Communicative competence in technical oral presentations through the lens of students and industry practitioners - Bhattacharyya, E. (2013)
Communicative competence remains an important skill expected of prospective graduates among employers. Despite its importance, this notion lacks clarity in its contextual definition. Such indefinite clarification has created apprehension among stakeholders like engineering students and industry practitioners' who are involved in the business workplace related oral communicative events such as technical oral presentations. In this study, engineering students are final year engineering students from the academic community who are involved in the delivery of final year technical project presentations. Industry practitioners, on the other hand, are professional engineers from the professional engineering community who have been selected to evaluate the students' final year engineering project presentations or technical oral presentations. Technical oral presentations constitute one of the many workplace related oral communicative events. Such concerns, as theoretically implied in the situated learning theory, if left unchecked, may result in the continued academia-industry practitioner discord over the said notion. The investigation is conducted to acknowledge the different interpretations of students and engineering practitioners in order to lessen the apparent academia-industry practitioner divide on communicative competence. The findings will discuss one of the sub-sets of communicative competence construct, i.e. presentations skills and attribute construct. Â© 2013 IEEE.